Prospective Randomized Comparison of Ovarian Blockade with Nafarelin Versus Leuprolide During Ovarian Stimulation with Recombinant FSH in an ICSI Program - Franco Jr, José G. (Kluwer Academic Publishers-Plenum Publishers, 2001)
Purpose: A prospective study was conducted to compare the efficiency of ovarian blockade with nafarelin versus leuprolide in a population whose indication for assisted reproduction was the male factor. Methods: A total of 238 patients were assigned at random to two types of treatment: Group I (119 aspirations), nafarelin (Synarel, Searle), 200 μg by the nasal route twice a day, and Group II (119 aspirations), leuprolide acetate (Lupron, Abbott), 0.5 mg by the subcutaneous route once a day. Both types of blockade were started during the 2nd phase (21st day of the menstrual cycle) and were continued until the day of HCG (5,000–10,000 IU). All patients received a fixed dose of recombinant FSH for 7 days and on the 8th day of stimulation the doses started to be adapted according to ovarian response. Results: Patients' age did not differ (p = 0.93) between Group I (34.1 ± 3.79) and Group II (34 ± 4.64). The number of oocytes retrieved from Group I (10.5 ± 5.93) was also similar (p = 0.57) to that retrieved from Group II (10.2 ± 6.36). In addition, there was no difference (p = 0.58) in the number of oocytes retrieved at Metaphase II between Group I (8.2 ± 4.61) and Group II (7.9 ± 5.2). Fertilization rates and embryo scores were similar (p = 0.81 and p = 0.25, respectively) for Group I (67.5% ± 21.3 and 34.4% ± 14.4) and Group II (68.1% ± 23 and 32.2% ± 14.7, respectively). In addition, pregnancy rates per puncture and per embryo transfer and implantation rates were similar for Group I (30.2, 31.3, and 16.2%, respectively) then compared with Group II (24.4, 25.2, and 12.6%, respectively) (p = 0.38, p = 0.37, and p = 0.22, respectively). Conclusions: Implantation and pregnancy rates per puncture and per embryo transfer are not statistically significant in the nafarelin group when compared with leuprolide group.